Adjectives and Modal Verbs Used in Horoscopes in Dawn Newspapers and their Impact on Readers: A Corpus-Assisted Study - Saqlain Hassan; Jamshaid Anjum; Zafar Ullah Shaheen (Corporum)
Horoscope columns are among the permanent features of English Newspapers in Pakistan,especially the Dawn. The current study aims to analyze the use of adjectives and modal verbs in the horoscope columns published in the Dawn news paperand their impact on the readers of these horoscope columns. This is a concurrent study comprising quantitative and qualitative data. The data for the first part are gathered from the official website of the Dawn Newspaper from March 04, 2024, till July 28, 2024. The data for the second part of the study are gathered with the help of a questionnaire from a purposive sample size of 20 males and females in equal proportion. Identification of adjectives and modal verbs is carried out with the help of the software Sketch Engine. The types of adjectives are categorized with the help of Classification Modal by Biber et al. (2002) whereas modal verbs are categorized with the help of the Dichotomy of ModalVerbs by Quirk and Greenbaum(2000). SystemicFunctional Grammar by Halliday (1985) has been used to investigate the meanings of adjectives within a clause. The responses from participants have been categorized with the help of Thematic Analysis of Braun and Clarke(2014). The findings of the study have revealed that mainly positive adjectives and modal verbs of possibility and prediction are used. Furthermore, these adjectives impact the readers' emotions positively and the modal verbs mainly provide a sense of hope and control regarding the future.